On a potential relationship between climate change and seismic activity of Earth, explained by a general model - Nutu, Catalin Silviu (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The scope of this paper is to investigate a potential relationship between the melting of icecap caused by the global warming and the seismic activity of Earth. The first step is the analysis of seismic activity data of the last decades, in order to establish if there is an ascending trend in the frequency or magnitude of the earthquakes, or to see whether this data exhibits certain features which could indicate a certain change in the pattern of the seismic activity of Earth. If there is an ascending trend in the seismic activity, the correlation with the amount of the melted icecap (expressed in both: square kilometers and tons) is to be further analyzed. If however, there is no such ascending trend but still, the data shows certain changes in its pattern, these changes will be analyzed and explained using the model proposed and presented in this paper. This general basic model describes and explains how reduction of pressure exerted by the melted icecap leads to a redistribution of gravity pressing forces on the earth’s crust and releases additional movement forces of the tectonic plates, thus causing an increased seismic activity.